Odpowiedzi

2010-01-19T18:21:27+01:00
A) 3(2x-1)-5(x-3)+6(3x-4)=83
6x-3-5x+15+18x-24=83
19x=83-15+24+3
19x=95
x=5

b)0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x+0,5x+25x-5-2,7x=6,5
23x=6,5
x=13/46

c) 0,3(0,4x-1,2)+0,36x=0,6
0.12x-0,36+0,36x=0,6
0,12x+0,36x=0,42
0,42x=0,42
x=1
1 5 1
2010-01-19T18:23:50+01:00
A) 3(2x-1)-5(x-3)+6(3x-4)=83
6x-3-5x+15+18x-24=83
6x-5x+18x=83+3-15+24
19x=95 /19
x=5

b) 0,2x+0,5x+5(5x-1)-2,7x=6,5
0,7x+25x-5-2,7x=6,5
-2x=6,5+5
-2x=11,5 /-2
x=-5,75

c) 0,3(0,4x-1,2)+0,36x=0,6
0,12x-0,36+0,36x=0,6
0,48x=0,6+0,36
0,48x=0,96
1 1 1
Najlepsza Odpowiedź!
2010-01-19T18:23:52+01:00
A) 3(2x-1)-5(x-3)+6(3x-4)=83
6x -3 -5x+15 +18x - 24 =83
6x-5x+18x = 83+3 -15 +24
19x= 95/ 19
x=5

b) 0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x +0,5x + 25x -5 - 2,7x =6,5
0,2x+0,5x+25x-2,7x =6,5 + 5
23x = 11,5 /23
x=0,5


c) 0,3(0,4x-1,2)+0,36x=0,6
0,12x -0,36 +0,36x = 0,6
0,48x=0,6 + 0,36
0,48 x= 0,96 / 0,48
x= 2
3 5 3